A Qualitative Examination of Leadership Styles and Their Impact on Employee Motivation in Indonesian Non-Profit Organizations - Hamsinah Hamsinah (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
This study delves into the realm of leadership within Indonesian non-profit organizations, recognizing the critical role it plays in influencing employee motivation. Against the backdrop of Indonesia's diverse and dynamic non-profit sector, characterized by its unique challenges and opportunities, this research seeks to explore the multifaceted relationship between leadership styles and the motivation levels of employees. The primary aim is to shed light on how different leadership approaches are perceived and practiced within this context, and their subsequent impact on employee motivation. To achieve this, a qualitative research methodology is employed, involving in-depth interviews, focus groups, and content analysis of relevant documents. Through a purposive sampling strategy, leaders and employees from a diverse range of Indonesian non-profit organizations are engaged in open discussions, providing rich insights into their experiences and perceptions. The findings reveal that leadership styles encompass a spectrum ranging from transformational to transactional, with varying implications for employee motivation. Transformational leadership is found to foster a culture of inspiration, intrinsic motivation, and commitment among employees, whereas transactional leadership tends to rely on extrinsic rewards and compliance. These findings offer valuable insights for non-profit organizations in Indonesia, aiding them in making informed decisions regarding leadership practices to enhance employee motivation and, consequently, organizational effectiveness.